High-Resolution Urban Flood Forecasting by Using a Coupled Atmospheric and Hydrodynamic Flood Models - Chen, Guangzhao; Hou, Jingming; Zhou, Nie; Yang, Shaoxiong; Tong, Yu; Su, Feng; Huang, Lei; Bi, Xu (Frontiers in Earth Science, 2020)
Flood forecasting is one of the most significant tools for reducing flood risk and avoiding the loss of life To solve the problem of low resolution and the short lead time of the traditional urban flood forecasting method, this work develops a novel high-accuracy and long lead time model through coupling the atmospheric and hydrodynamic models. The GRAPE_MESO model is applied as an atmospheric model for predicting rainstorms. To improve reliability, a reconstructed method is put forward to correct predicted rainstorm data. The reconstructed predicted rainstorm is then used as input data for the hydrodynamic flood model. Finally, the urban flood inundation process was forecasted by the coupled atmospheric and flood model. Though applying the coupled model at Fengxi New Town (China), the performance is evaluated for realistic urban flood forecasting. The results show that the coupled modeling system can predict the urban flood inundation process with high-resolution and a long lead time.